Appendix 2.7: Confidential Cable from the US Embassy in Manila, “Congressman Solarz Calls on President Marcos,” 26 November 1976 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Here, Marcos is reported as saying that there is “some truth” to the Amnesty International Report detailing human right abuses—including torture—by the military under martial law. However, he insisted that such abuses were not government policy.